2008
DOI: 10.4012/dmj.27.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermediate Fiber Layer on the Fracture Load and Failure Mode of Maxillary Incisors Restored with Laminate Veneers

Abstract: This study evaluated the fracture load and failure mode of various veneer materials cemented with or without the addition of a fiber-reinforced composite (FRC) layer at the adhesive interface. Sixty intact incisors were randomly divided into three groups. Group 1 was fabricated with the heat-press technique (IPS Empress 2); Group 2 with the copy milling technique (ZirkonZahn); and Group 3 with the direct or indirect composite technique (Z250) -and specimens were cemented either with or without FRC at the adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
(58 reference statements)
2
18
0
1
Order By: Relevance
“…Previous reports have attributed the complex failure behavior to a change in the interface dynamics, whereby the latter resulted from the fibers added to the tooth-restoration interface 18,29) . The results of the current study were in good agreement with previous reports, which showed changes in failure mode despite the lack of increase in static adhesive strength 18,21,29,30) . Similarly, the final failure loads in the current study were not statistically different among the test groups -however, significant differences were seen in the load-deflection graphs as well as in their failure modes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous reports have attributed the complex failure behavior to a change in the interface dynamics, whereby the latter resulted from the fibers added to the tooth-restoration interface 18,29) . The results of the current study were in good agreement with previous reports, which showed changes in failure mode despite the lack of increase in static adhesive strength 18,21,29,30) . Similarly, the final failure loads in the current study were not statistically different among the test groups -however, significant differences were seen in the load-deflection graphs as well as in their failure modes.…”
Section: Discussionsupporting
confidence: 83%
“…This allowed monomers with the same dissolving parameter as PMMA to diffuse into the polymer matrix. In accordance with a previous report, the failure analysis of the FRC groups confirmed good adhesion between the laminate veneer and the luting agent 30) . Despite occurrences of adhesive failure between the PFC veneer and luting agent, adhesive failures between the FRC and luting agent were not common in this study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent years have seen a dramatic increase in the use of fiber-reinforced composites (FRCs) for chairside periodontal splints 11) , fixed partial dentures 11) , post-core systems 12) , and orthodontic applications 13) . For direct or indirect restorations such as composite inlays 14) and laminate veneers 15) , insertion of an intermediate FRC layer/substructure at the interface was found to reduce microleakage and increase fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cast was poured using type IV dental die stone. 9,10 Stone dies were carefully separated from the impression and teeth were randomly divided into two subgroups: 1. Group I: Veneers fabricated with light (n = 10) (light-emitting diode light-curing unit) are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%